COMPARATIVE STUDY OF TRADITIONAL PWM INVERTERS AND MULTILEVELS INVERTERS (Journal of Engineering, 2008)
The need of higher powers in electrical drives has forced the researchers to develop new power source possibilities. Multilevel inverters have been presented as a cost effective solution for various high voltage and high power applications including power quality and motor drive problems. The traditional pulse width modulated (PWM) Inverter does not completely eliminate the unwanted harmonics in the output waveform. Using the multilevel inverter as an alternative to traditional PWM inverters for electric motor drive applications is investigated. The concept of the Optimized Harmonic Elimination Stepped-Waveform (OHESW) technique for a multilevel inverter is presented. The effectiveness of this technique in minimizing the inverter switching losses and its output voltage harmonic content which cause reducing harmonic losses and torque pulsations of an induction motor fed form is investigated analytically. Comparison between the Selective Harmonic Eliminated PWM (SHEPWM) as a traditional PWM technique for three-level inverter and the OHESW technique for multilevel inverter with regard to the switching losses, harmonic distortion, additional harmonic losses in the motor and the pulsating torques is also presented.